Análisis de la empleabilidad de los profesionales graduados de la carrera de hotelería y turismo de la UTBG en las organizaciones del sector turístico y hotelero - Segura Rodríguez, Joseph Alfonso (2021)
This research refers to the existing problems with the employability of professionals graduated from the hospitality and tourism career of the years 2018, 2019 and 2020 of the UTB, to achieve their inclusion in the workplace since, for various reasons, these graduates in tourism are not working or are working in other areas of knowledge that do not belong to their professional profile. It should be noted that the low demand for jobs that exists in the tourism sector is one of the causes that affects the professionals graduated from the hospitality and tourism career of the UTB, this can be improved through public sector organizations because these are the entities in charge of designating the convenient economic cost to generate tourist areas and thus increase the job market. In this sense, after surveying 60 tourism professionals through Google drive surveys, the following findings could be determined, that graduates have a high deficit in the English language and little interest in training